Analisis pemasaran rajungan (portunus pelagicus) di Desa Tanjung Bunga Kecamatan Wawolesea Kabupaten Konawe Utara - Dafirudin; Budiyanto; Mansyur, Akhmad (Universitas Halu Oleo, 2021)
This research was conducted in the village of Tanjung Bunga Wawolesea District North Konawe Regency from February to March 2019. The aim of this research is to determine the marketing channels and marketing margins of swimming crab.The number of respondents in this study is 10 persons. Data obtained through the census methods with direct interviews using a questionnaire. The research variables are measured and observed was prices, margins, and costs.The results showed there is 1 (one) marketing channels of swimming crab, which is fisherman will sell their catch to traders and then traders will process the crab into semi-finished goods and shipped to PT. Ocean Cham Seafood in Kendari. This company will distribute to the company in the city of Makassar. Total costs incurred by traders was Rp405.000 and sell to the big traders was Rp560.000. Amount margin in traders amounting Rp80,000/kg, and wholesalers Rp30,000/kg. Marketing margins at traders are greater than the wholesalers because of processing activities.